2010
DOI: 10.1007/s10592-010-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of the endangered endemic Sambucus palmensis Link (Sambucaceae) from the Canary Islands

Abstract: Five polymorphic microsatellites (simple sequence repeat; SSR) markers were used to estimate the levels of genetic variation within and among natural populations from different islands of the endangered endemic from the Canary Islands Sambucus palmensis Link (Sambucaceae). Genetic data were used to infer potential evolutionary processes that could have led to present genetic differentiation among islands. The levels of genetic variability of S. palmensis were considerably high; proportion of polymorphic loci (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
1
22
1
1
Order By: Relevance
“…Support for this interpretation comes from the observation that, contrary to our results in R. microcarpa , low values of genetic diversity were found for sexually reproducing Canarian endangered species ( H e = 0.2 for Anagyris latifolia , González-Pérez et al 2009; H o = 0.113, H e = 0.306 for Lotus kunkelii , Oliva-Tejera et al 2006; H o = 0.100, H e = 0.112 for Cistus chinamadensis ssp. gomerae , Batista et al 2001), while values of genetic diversity were similar to those found in this study for other endangered clonal species such as the Canarian endemic Sambucus palmensis ( H o = 0.550, H e = 0.499; Sosa et al 2010) and the Southern Appalachian endemic Spiraea virginiana ( H o = 0.503, H e = 0.391; Brzyski and Culley 2011). …”
Section: Discussionsupporting
confidence: 88%
“…Support for this interpretation comes from the observation that, contrary to our results in R. microcarpa , low values of genetic diversity were found for sexually reproducing Canarian endangered species ( H e = 0.2 for Anagyris latifolia , González-Pérez et al 2009; H o = 0.113, H e = 0.306 for Lotus kunkelii , Oliva-Tejera et al 2006; H o = 0.100, H e = 0.112 for Cistus chinamadensis ssp. gomerae , Batista et al 2001), while values of genetic diversity were similar to those found in this study for other endangered clonal species such as the Canarian endemic Sambucus palmensis ( H o = 0.550, H e = 0.499; Sosa et al 2010) and the Southern Appalachian endemic Spiraea virginiana ( H o = 0.503, H e = 0.391; Brzyski and Culley 2011). …”
Section: Discussionsupporting
confidence: 88%
“…Compared with that in other endangered endemic perennial species [e.g., Berchemiella wilsonii var. pubipetiolata; H E = 0.503 (Kang et al, 2008) and Sambucus palmensis; H E = 0.500 (Sosa et al, 2010)], the genetic diversity detected in A. sinensis was higher.…”
Section: Discussionmentioning
confidence: 96%
“…Given their small population size and endemic character, we had expected A. sinensis populations to be genetically impoverished (Sosa et al, 2010). To determine whether this rare species exhibits low diversity, a measure or standard for comparison is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when considering island biodiversity, it is necessary to give particular attention to genetic diversity and to the factors promoting its evolution and differentiation within each taxa, allowing the conservation of micro-niches to preserve the required isolation for the maintenance of that speciation (e.g. Sosa et al, 2010;Schaefer et al, 2011). This question is critical when analysing continuity and heterogeneity at the island level, determining that, as important as the preservation of a viable population, it is critical to ensure, simultaneously, its intrinsic micro-diversity and the resulting ability to respond biologically and physically to disturbances.…”
Section: Challenges To Planning and Management In The Context Of Smalmentioning
confidence: 99%